Triple negative breast cancer in the era of miRNA. (January 2021) - Sabit, Hussein; Cevik, Emre; Tombuloglu, Huseyin; Abdel-Ghany, Shaimaa; Tombuloglu, Guzin; Esteller, Manel
Graphical abstract: Abstract: The objective of this review is to elucidate the role of miRNAs in triple negative breast cancer (TNBC). To achieve our goal, we searched databases such as PubMed, ScienceDirect, Springer, Web of Science and Scopus. We retrieved up to 1233 articles, based a rigorous selection criterion, only 197 articles were extensively reviewed. We selected articles only addressing TNBC, but not other types of breast cancer, with the employed approach being miRNA analysis and/or profiling. Our extensive review resulted in grouping of miRNAs into categories in which specific members of miRNAs have roles in specific mechanism in TNBC i.e., carcinogenesis, invasion, metastasis, apoptosis, diagnosis, prognosis, and treatment. TNBC is an aggressive subtype of breast cancer; therefore, different approaches for accurate diagnosis, prognosis and treatment are needed. In this review we summarize the up-to-date miRNA profiling, prognostic, and therapeutic findings that add to the route of controlling TNBC.